Strategy to Build A Sustainable Business Ecosystem by Optimizing Usage QR Code From Sudirman Street Food Bandung West Java - Lavinia Jennifer; Budi Setiawan (CV. Syntax Corporation Indonesia, 2023)
Strategy for building a sustainable business ecosystem using QR Code in Sudirman Street Food Bandung can increase people's attraction to SudirmanStreet Food Bandung. QR Code ordering can minimize errors in the food ordering system, QR Code itself also has features such as monitoring income and expenses because QR Code can be a means of payment. QR Code in Sudirman Street Food Bandung is also used for the payment system and also for the ordering system. In this research, the strategy for building a sustainable business ecosystem is by using QR Code in Sudirman Street Food Bandung uses qualitative methods with a case study approach, and carries out sampling techniques using the Slovin formula while data collection techniques use observation and interview techniques. The data analysis used is a qualitative descriptive analysis technique to identify challenges and opportunities in use QR code in the food and beverage business in Sudirman Street Food Bandung. The analysis method used is factor analysis and SWOT analysis. Based on analysis of problems found at the location Sudirman Street Food Bandung found that use QR Code for orders in Sudirman Street Food Bandung is no longer used for various reasons in terms of sellers and visitors in Sudirman Street Food Bandung, therefore various innovations have been discovered that can optimize and revive a sustainable business ecosystem by using QR Code as an ordering method in Sudirman Street Food Bandung, so that a sustainable business ecosystem can be implemented in Sudirman Street Food Bandung.